Handbook of feminist family studies - Lloyd, Sally A.; Few, April L.; Allen, Katherine R.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
This handbook presents the important theories, methodologies and practices in feminist family studies. The editors showcase feminist family scholarship, providing both a retrospective and a prospective overview of the field.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Women -- Social conditions; Families; Sex role; Feminist theory; Electronic books